A study on fire retardancy and durability performance of bagasse fiber/polypropylene composite for outdoor applications. (September 2013) - Hemmati, Farkhondeh; Garmabi, Hamid
Wood–plastic composites (WPCs) and natural fiber composites (NFCs) are increasingly used in decking applications, where exterior exposure can lead to photodegradation and fungal deterioration. Since the fire retardancy is another proficiency concern of these composites, bagasse/polypropylene composites were produced by incorporation of commercially available additives including flame retardants, ultraviolet (UV) stabilizer, antifungal agent and color masterbatches. The addition of the flame retardant which decomposed at high temperature could result in NFC with significant decrease in burning rate (up to 98%) compared to the composite without flame retardant. Simultaneous effects of antifungal agent and green masterbatch lead to complete suppression of the fungal growth and reproduction on composites exposed to either Lentinus edodes, Pleurotus eryngii strain or each of them accompanied by Trichoderma sp. fungus. Durability performance followed by discoloration, mechanical properties loss and surface chemistry variation depended on all additives used. The results indicated that darker color pigment improved color stability and caused much lower fading for UV-stabilized NFC in comparison to the nonstabilized unpigmented composite.